On importance of pink salmon reproduction for freshwater ecosystems - V. I. Radchenko (Известия ТИНРО, 2024)
The report is based on observations of food composition in stomachs of common predatory fish species caught during recreational fisheries in the Fraser River basin, in particular Lake Morris (British Columbia, Canada), as cutthroat Oncorhynchus clarkii, mountain whitefish Prosopium williamsoni, and northern pikeminnow Ptychocheilus oregonensis. Up to 164, 126 and 28 fry of pink salmon Oncorhynchus gorbuscha were found in the stomachs of the listed fish species, respectively, during pink salmon downstream migration in April — early May. In this season, these species can consume a significant portion of their annual food ration, especially in energy terms. In the lake under con- sideration, these three predators are capable to eliminate pink salmon fry from the spawning of about 2,390 pink salmon in a small inflowing stream. Since the spawners of only the odd-years broodline of pink salmon reproduce in the rivers of the southern Pacific coast of Canada, the migration of their juveniles creates a significant difference in feeding conditions for predatory fish in adjacent years.